The equality of rights and responsibilities of men and women in Islam - Abd Rahman, Saodah (2014)
Islam acknowledges the role of women in developing a community. Islam also explaines that women are an important factor for the advancement and development of a nation. Thus, the religion of Islam gives equal rights to both men and women in performing their duties or responsibilities as stated in the Holy Qur’an and Sunnah. Islam provides many privileges towards women including the freedom to seek knowledge, to voice out their rights and opinions as a daughter, wife, and mother, and as part of the community. The rights and responsibilities of women are based upon the fitrah or natural tendency and of the Shari’ah legislation. In addition, Islam also introduces laws to protect women from defamation, insults and false accusations.